2015
DOI: 10.1039/c5ee02214b
|View full text |Cite
|
Sign up to set email alerts
|

Renewable fuels from concentrated solar power: towards practical artificial photosynthesis

Abstract: There is intense interest in the solar driven conversion of water to hydrogen as a means of achieving the sustainable generation of a practical fuel. It is widely considered that such "Artificial Photosynthesis" processes need to achieve an energy conversion efficiency exceeding 10 % to have practical impact. Although some solar--driven fuel generating systems have reached efficiencies as high as 18 %, they are often based on precious metal catalysts, or offer only limited stability.We describe here a system t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
99
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(99 citation statements)
references
References 27 publications
0
99
0
Order By: Relevance
“…It becomes interesting for us to study whether similar nickel oxide/nickel heterostructures could be grown on RGO. Furthermore, because nickel oxide/nickel can also serve as an active OER catalyst 13,[29][30][31][32][33] the OER properties of the nickel oxide/nickel heterostructures on RGO are worthy of further investigation.In this report, graphene oxide (GO) was used as a scaffold to support Ni-based nanoparticles and the resulting Ni nanocomposites were analyzed by X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), and scanning electron microscopy (SEM), and further tested as OER electrocatalysts. It was confirmed that nickel oxide/nickel heterostructures can be grown on RGO membranes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It becomes interesting for us to study whether similar nickel oxide/nickel heterostructures could be grown on RGO. Furthermore, because nickel oxide/nickel can also serve as an active OER catalyst 13,[29][30][31][32][33] the OER properties of the nickel oxide/nickel heterostructures on RGO are worthy of further investigation.In this report, graphene oxide (GO) was used as a scaffold to support Ni-based nanoparticles and the resulting Ni nanocomposites were analyzed by X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), and scanning electron microscopy (SEM), and further tested as OER electrocatalysts. It was confirmed that nickel oxide/nickel heterostructures can be grown on RGO membranes.…”
mentioning
confidence: 99%
“…It becomes interesting for us to study whether similar nickel oxide/nickel heterostructures could be grown on RGO. Furthermore, because nickel oxide/nickel can also serve as an active OER catalyst 13,[29][30][31][32][33] the OER properties of the nickel oxide/nickel heterostructures on RGO are worthy of further investigation.…”
mentioning
confidence: 99%
“…However, this system suffered from the lack of stability of the perovskite photovoltaic cells. More recently, another modular system that utilizes concentrated solar power and an electrode based on the earth-abundant material Ni showed a solar energy to fuel energy conversion efficiency of 22.4 % under various electrolyte conditions [27]. The overall performance of such a system can be optimized by choosing the right electrode material and particle size, as well as the right electrolyser conditions (e.g.…”
Section: Generation Of Hydrogen and Oxygen By Water Splittingmentioning
confidence: 99%
“…The overall performance of such a system can be optimized by choosing the right electrode material and particle size, as well as the right electrolyser conditions (e.g. electrolyte, operating temperature) [27].…”
Section: Generation Of Hydrogen and Oxygen By Water Splittingmentioning
confidence: 99%
“…A number of reviews have highlighted the importance of these technologies (e.g., Graves et al 2011;Newman et al, 2012;van der Giesen et al, 2014;Herron et al, 2015;Kumar et al, 2016). Promising progress has been demonstrated for solar H 2 from water splitting (Rongé et al, 2014;Ager et al, 2015;Bonke et al, 2015;Jia et al, 2016;Shi et al, 2016), though many challenges remain. However, carbon-based fuel production requires both the reduction of CO 2 and the oxidation of water, and is a far more challenging undertaking than the H 2 production alone.…”
Section: Challenges and Opportunities For (Photo)electrochemical Prodmentioning
confidence: 99%